ChemInform Abstract: Montmorillonite K‐10 Catalyzed Green Synthesis of 2, 6‐Unsubstituted Dihydropyridines as Potential Inhibitors of PDE4. Issue 33 (25th July 2013) - Reddy, T. Ram; Reddy, G. Rajeshwar; Reddy, L. Srinivasula; Meda, Chandana Lakshmi T.; Parsa, Kishore V. L.; Kumar, K. Shiva; Lingappa, Y.; Pal, Manojit
Abstract A variety of 2, 6‐disubstituted dihydropyridines (IV) (15 examples) is obtained in a multicomponent reaction of anilines, aldehydes and 3, 3‐diethoxypropionate (I) using montmorillonite K10 as cheap and reusable catalyst.